Nursing home residents: the dimension of frailty - Raposo, P.; Nogueira, D.; Reis, E.; Serrasqueiro, R. M. (Topics in Geriatric Rehabilitation, 2017)
Background: Frailty is a state of increased vulnerability with multisystem loss of physiologic reserves and decreased response to stressors, predicting adverse health outcomes. The phenotype of frailty is characterized by unintentional weight loss, self-reported exhaustion, weakness (low grip strength), slow walking speed, and low physical activity. This study aimed at assessing the prevalence and characteristics of frailty in a sample of institutionalized older people to identify a target intervention group. Methods: This is a descriptive cross-sectional and correlational study. Participants were 226 men and women living in nursing home facilities. Frailty was assessed using the phenotype of frailty. Sociodemographic, health status, physical and cognitive function, and depression data were collected. Relations between variables were analyzed using parametric (t test, Pearson coefficient) and nonparametric (chi-square and Spearman coefficient) tests. A multiple linear regression model was applied to assess the relationship between the frailty criteria and a set of predictor variables. Results: Assessment of frailty was possible in 35.3% of the subjects and 41.5% were found frail, 52.1% prefrail, and 6.4% nonfrail. Three frailty criteria had higher prevalence: weakness (76.6%), low physical activity (61.7%), and low walking speed (52.1%). The number of frailty criteria per subject was significantly correlated with cognitive status and depressive symptoms, and there was weak, though significant, correlation with the Barthel Index. Participants in frailty tests had a better functional and cognitive state than those unable to participate. No significant difference in depressive symptoms was found between these 2 groups. The multiple regression model explained only 21.6% of the variation of frailty. Conclusions: Subjects revealed low social status, advanced age comorbidity, and multifactorial incapacity. In a nursing home setting, frail and prefrail elderly stand out as a subset in the sample with higher functional status, as opposed to the usual findings in community-dwelling older adults. These facts should help recognize them as a target intervention group, as frail elderly are vulnerable and their needs might be underestimated in a setting where highly dependent people represent a huge burden for caretakers. Targeted interventions may improve their condition, prevent adverse health events, and preserve quality of life.